Do MEFV mutations influence arterial stiffness in FMF patients? - Ulu, Memnune Sena; Acay, Akif; Ahsen, Ahmet; Yuksel, Şeref; Acartürk, Gürsel; Solak, Mustafa (International Journal of Research in Medical Sciences, 2017)
Background: Pulse wave velocity (PWV) is the most used technique to evaluate the arterial elasticity, which is an early indicator of atherosclerosis. We aimed to evaluate if MEFV Mutations influence arterial stiffness in patients with Familial Mediterranean fever (FMF) Methods: 70 patients diagnosed with FMF and 50 age-and sex-matched controls were included in the study. Genetic analysis of the patients was performed. After the measurement of PWV; the presence of AS was determined. Results: Mean PWV value and arterial stiffness frequency of FMF patients were significantly higher than the control group (p <0.001, p <0.001) respectively. In addition, FMF patients with M694Vmutations had higher PWV values and arterial stiffness frequency than those with other mutations<s>.</s> (p=0.045), (p=0.001). There were no differences within all genetic mutation types in terms of arterial stiffness frequency. Conclusions: As a result, due to subclinical inflammation in FMF patients, they have risk for cardiovascular complications. These patients especially those with M694Vmutations have to be followed more closely because of increased cardiovascular risk and PWV measurements may be a good tool to detect early development of atherosclerosis.